Placental small extracellular vesicles: Current questions and investigative opportunities. (December 2020) - Sadovsky, Yoel; Ouyang, Yingshi; Powell, Juliana S.; Li, Hui; Mouillet, Jean-Francois; Morelli, Adrian E.; Sorkin, Alexander; Margolis, Leonid
Abstract: The discovery of regulated trafficking of extracellular vesicles (EVs) has added a new dimension to our understanding of local and distant communication among cells and tissues. Notwithstanding the expanded landscape of EV subtypes, the majority of research in the field centers on small and large EVs that are commonly termed exosomes, microvesicles and apoptotic cell-derived vesicles. In the context of pregnancy, EV-based communication has a special role in the crosstalk among the placenta, maternal and fetal compartments, with most studies focusing on trophoblastic EVs and their effect on other placental cell types, endothelial cells, and distant tissues. Many unanswered questions in the field of EV biology center on the mechanisms of vesicle biogenesis, loading of cargo molecules, EV release and trafficking, the interaction of EVs with target cells and the endocytic pathways underlying their uptake, and the intracellular processing of EVs inside target cells. These questions are directly relevant to EV-based placental-maternal-fetal communication and have unique implications in the context of interaction between two organisms. Despite rapid progress in the field, the number of speculative, unsubstantiated assumptions about placental EVs is concerning. Here we attempt to delineate existing knowledge in the field, focusing primarily on placental small EVs (exosomes). We define central questions that require investigative attention in order to advance the field.